Advanced drug delivery platforms target cancer stem cells - MirAhmad Mazloomi; Abolfazl Doustmihan; Sajjad Alimohammadvand; Hamed Hamishehkar; Michael R. Hamblin; Rana Jahanban Esfahlan (Asian Journal of Pharmaceutical Sciences, 2025)
Cancer stem cells (CSCs) are a major challenge in cancer therapy. Stem cell-like cells form a unique subpopulation within many tumors, which govern the degree of malignancy by promoting metastasis, recurrence, heterogeneity, and resistance to drug and radiation. Furthermore, these cells can persist in patients even after undergoing multiple cycles of conventional cancer therapy via dormancy, where they no longer dividing but remain active. These may cause cancer recurrence at any time, even years after a supposed cure, and remain invisible to the immune system. Targeting specific surface markers, signaling pathways and tumor microenvironment, which all have a significant effect on CSC function and maintenance, could help to eradicate CSCs and improve patient survival. Combinations of traditional therapies with nano-based drug delivery systems can efficiently target CSCs. Considering the biology and properties of CSCs, we classify recent approaches involving nanoparticle engineering, extracellular matrix modulation, cocktail strategies, multi-stage therapy, CSC defanging, Trojan horse systems, targeted therapy and organelle targeting. We highlight the most recent advances in nanocarrier design and drug delivery technologies to target CSCs, combined with conventional treatment in preclinical and clinical trials. The prospects of these approaches for CSCs elimination and recurrent cancer treatment are discussed.